Who does not participate in telehealth trials and why? A cross-sectional survey - Foster, Alexis; Horspool, Kimberley; Edwards, Louisa; Thomas, Clare; Salisbury, Chris; Montgomery, Alan A.; O'Cathain, Alicia (BioMed Central, 2015)
Background Telehealth interventions use information and communication technology to provide clinical support. Some randomised controlled trials of telehealth report high patient decline rates. A large study was undertaken to determine which patients decline to participate in telehealth trials and their reasons for doing so.